The Effectiveness of the ETLE Program in Enforcement of Traffic Violations at the Polda Metro Jaya - Alexander Timothi Simanjuntak (Advances in Police Science Research Journal, 2021)
This research is motivated by the establishment of a program conducted by the Ditlantas Polda Metro Jaya in November 2018 in the form of Electronic Traffic Law Enforcement (ETLE) to help traffic law enforcement activities in Metro Jaya Police Department to deal with the increasing number of traffic violations that have occurred in the DKI Jakarta jurisdiction. The results of the study found that the ETLE Program still has flaws in its implementation strategy, a definite basic legal component, facilities, infrastructure / facilities, internal supervision, and evaluation of the performance of implementers have not met the standards. Factors that influence innovation, communication channels, and social systems become inhibitory factors. Effective efforts that have been done include the implementation of a deeper socialization to understand the ETLE program, as well as extra energy in the identification of violations caught by the camera and not read the identity of the vehicle. Based on the results of the study, the researchers suggested to improve the installation of CCTV on several roads in the jurisdiction of Polda Metro Jaya. Expanding information about the use, the police and the government of Polda Metro Jaya District can work together and involve the community directly in addressing and reducing the rate of violations and traffic accidents. Determination of legal basis that is specific to the ETLE Program to launch active legal and administrative crackdowns that facilitate the community.